1977
DOI: 10.2307/1935611
|View full text |Cite
|
Sign up to set email alerts
|

A Complex Community in a Simple Habitat: An Experimental Study with Bacteria and Phage

Abstract: Continuous culture populations of the bacterium especially coli and its virulent virus T7 have been studied as a model of a predator—prey in a simple habitat. These organisms maintain apparently stable states of coexistence in: (1) a phage—limited situation where all of the bacteria are sensitive to the coexisting virus and the sole, and potentially limiting carbon source, glucose, is present in excess; and (2) a resource—limited situation where the majority of the bacteria are resistant to these phage and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
249
3
1

Year Published

1988
1988
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 259 publications
(264 citation statements)
references
References 23 publications
11
249
3
1
Order By: Relevance
“…An alternative hypothesis would suppose that the bacteria develop phage resistance during the epidemic (15,16). Epidemics may provide increased opportunity for the required mutations to arise during exponential growth occurring within infected individuals.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative hypothesis would suppose that the bacteria develop phage resistance during the epidemic (15,16). Epidemics may provide increased opportunity for the required mutations to arise during exponential growth occurring within infected individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Key to our approach is the assumption that clones differ in their life history traits and that there are costs for low vulnerability and high offense. Trade-offs between species traits have been observed in predators (31,32) and prey (13,33,34). In the clonal model, low-vulnerability prey clones are consumed at a lower rate than high-vulnerability clones at the cost of a lower growth rate (i.e., a lower intraspecific competitive ability).…”
Section: Significancementioning
confidence: 99%
“…Recent studies of bacterium-phage coevolution have found that infectivity range is correlated with the number of amino acid changes in tail fibers relative to the ancestral genotype , providing further support for the GFG framework. However, coevolutionary arms races are unlikely to be maintained indefinitely as fitness costs associated with generalism (usually in the form of lower growth/infectivity rates) can reduce selection for broad ranges (Chao et al 1977;Webster and Woolhouse 1999;Sasaki 2000;Bohannan et al 2002;Lopez-Pascua and Buckling 2008;Poullain et al 2008). Sasaki (2000) predicted that fitness costs will lead to fluctuations between specialism (narrow range) and generalism (broad range), but empirical observations suggest that fitness costs may instead lead to fluctuating selection among genotypes with similar ranges .…”
Section: Introductionmentioning
confidence: 99%